Case Report: Anterior Cruciate Ligament Calcification in a Patient With Chondrocalcinosis: Micro-Computed Tomography Presentation - Grassi, Alberto; Dal Fabbro, Giacomo; Fini, Milena; Zaffagnini, Stefano; Parrilli, Annapaola (Frontiers in Surgery, 2021)
In this case report, an incidental postoperative diagnosis of anterior cruciate ligament (ACL) calcification, associated with calcification of posterior cruciate ligament (PCL) and lateral meniscus insertions, was made using micro-computed tomography (μCT) technology in a knee specimen obtained during a total knee replacement (TKR) surgery due to painful tri-compartmental osteoarthritis (OA) with chondrocalcinosis signs at preoperative X-ray. Anterior cruciate ligament calcification is an uncommon finding, and conventional X-ray and MRI are not so helpful in its identification. μCT scan, in contrast, is of interest because it provides highly spatial three-dimensional information with excellent visualization of bones and calcifications. The μCT technology used in this case report allowed us to perform a detailed analysis and a 3-D reconstruction of the calcium pyrophosphate dihydrate (CPPD) crystal deposition about the knee without the need to section the specimens into slice as performed in previous studies. The 3-D model obtained with μCT scan permits to gain more insight into the shape of the calcification within the fibers of the ligamentous structures of the joint.